Dakwah Multikultural Pesantren Ngalah dalam Meredam Radikalisme Agama - Saifulah Saifulah (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2014)
The emergence of radical ideology and violent movement that employ terror as a means to achieve goals has become prevalent in today?s life. This has been the subject matter widely discussed by a great deal of scholars, Muslims and non-Muslims alike. Among Muslims themselves, such a phenomenon raises anxieties. If this is not taken care of appropriately, it will have a negative impact on humanity, particularly Muslims who live in Muslim minority countries where Islamophobia is widespread. Along with this, pesantren as one of the oldest Muslim institutions of learning has a significant role in eliminating radicalism and terrorism in the name of religion. As far as the writer is concerned, efforts at dealing with radicalism have not been conducted seriously, although some pesantren have taken part in such projects. This paper tries to offer an alternative solution to eradicate religious radicalism and terrorism based on the experiences of Pesantren Ngalah by implementing the strategy of multicultural learning.